2020
DOI: 10.1002/jbmr.4663
|View full text |Cite
|
Sign up to set email alerts
|

Hip Fractures in Older Adults Are Associated With the Low Density Bone Phenotype and Heterogeneous Deterioration of Bone Microarchitecture

Abstract: Femoral neck areal bone mineral density (FN aBMD) is a key determinant of fracture risk in older adults; however, the majority of individuals who have a hip fracture are not considered osteoporotic according to their FN aBMD. This study uses novel tools to investigate the characteristics of bone microarchitecture that underpin bone fragility. Recent hip fracture patients (n = 108, 77% female) were compared with sex-and age-matched controls (n = 216) using high-resolution peripheral quantitative computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Image data captured in vivo with human participants were aggregated from four separate studies performed in our lab exploring bone microarchitecture by HR-pQCT, which were: a normative study [17], a hip fracture study [18], and two studies with high-performance athletes [19], [20]. All images were obtained using HR-pQCT (XtremeCT II, Scanco Medical AG, Brütisellen, Switzerland) with the standard fixed offset in vivo scan protocol at standard scan sites for the distal radius and tibia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Image data captured in vivo with human participants were aggregated from four separate studies performed in our lab exploring bone microarchitecture by HR-pQCT, which were: a normative study [17], a hip fracture study [18], and two studies with high-performance athletes [19], [20]. All images were obtained using HR-pQCT (XtremeCT II, Scanco Medical AG, Brütisellen, Switzerland) with the standard fixed offset in vivo scan protocol at standard scan sites for the distal radius and tibia.…”
Section: Methodsmentioning
confidence: 99%
“…Turning to bone volume fraction, we first note that this parameter is defined as the ratio of bone volume to total volume within a compartment. We hypothesize that within a unit volume, this ratio will scale as some power of the ratio of the trabecular thickness to the sum of trabecular thickness and separation: Image data captured in vivo with human participants were aggregated from four separate studies performed in our lab exploring bone microarchitecture by HR-pQCT, which were: a normative study [17], a hip fracture study [18], and two studies with high-performance athletes [19], [20]. All images were obtained using HR-pQCT (XtremeCT II, Scanco Medical AG, Brütisellen, Switzerland) with the standard fixed offset in vivo scan protocol at standard scan sites for the distal radius and tibia.…”
Section: Theoretical Relationshipsmentioning
confidence: 99%
“…For example, three bone microarchitecture phenotypes associated with different levels of osteoporotic fracture risk were identified using data from the BoMIC cohort. 15 In addition, a recent study 16 suggested that heterogeneous microarchitectural deterioration leading to the formation of void spaces may play a role in the determination of bone fragility, on top of low bone mineral density.…”
Section: Primary Osteoporosismentioning
confidence: 99%
“…This study suggests that certain mechanisms of microarchitectural deterioration (e.g., cortical versus trabecular deterioration) may be more detrimental for a specific phenotype, as they may not be able to compensate mechanically through adaptation of other traits. A retrospective study of hip fracture patients further verified a strong relationship between fractures at the hip, a major osteoporotic fracture site, and the low-density phenotype, but highlighted sex-specific differences in terms of distribution between male and female hip fracture patients across the microarchitectural phenotypes [ 37 •].
Fig.
…”
Section: Bone Phenotypes and Their Role In Fracture Risk Assessmentmentioning
confidence: 99%
“…The left figure of each example depicts trabecular (green) and cortical (grey) microarchitecture and the right figures of each example depict porosity (red) in the cortical compartment (transparent grey). Examples are from population-based cohorts courtesy of the Bone Imaging Lab, Calgary, Canada [ 37 , 48 ]. B Three-dimensional HR-pQCT reconstructions of distal tibia scans showing examples of the variability of bone phenotypes in females with type I osteogenesis imperfecta [ 67 ] …”
Section: Metabolic and Rare Bone Diseases In The Context Of Bone Phen...mentioning
confidence: 99%